Türkçe kaynak metinlerin Türkçe öğretiminde kullanılabilirliği - Özden, Mehtap (My University, 2009)
Çalısma, Türkçe kaynak metinlerin dil eğitiminde, kültür ve değerlerin çocuklara aktarılmasında kullanılma imkânının tespiti için yapılmıstır. Türkçe kaynak metinlerden 14. yüzyıla ait mesnevî türü eserler ve bu tür eserlerin içinde yer alan kısa hikâyeler malzeme olarak belirlenmistir. 14. yüzyıl ve mesnevî türü eserlerle yapılan sınırlandırmadan sonra kaynak metinlerin taranması asamasına geçilmistir. Bu yüzyıla ait baslıca eserler taranmıs ve Anadolu sahasında yazılan ilk iki büyük eser Mantıku’t-Tayr ve Garîb-nâme adlı mesnevîlerden metinlerin seçilmesine karar verilmistir. Bu iki mesnevîden on dört metin seçilmis, seçilen metinlerde kullanılan kelimelerde anlam karısıklığını önlemek için metinlerin eski yazıları da okunarak çeviri yazıları, dil içi çevirileri yapılmıs, sözlükleri hazırlanmıs ve nesre dönüstürülmüslerdir. Hikâyeler yazıldığı dönem olan 14. yüzyıl resim sanatını yansıtan resimlerle resimlenmistir. Metinler, okunabilirliklerinin anlasılması için Türkçe eğitimi alanında çalısan uzmanlara, çocuk edebiyatı yazarlarına, Türkçe eğitimi lisans öğrencilerine ve 11-15 yas arasındaki çocuklara okutulmustur. Bu asamadan sonra metinlerde bazı düzenlemeler yapılmıs ve daha sonra 11-15 yas arasındaki farklı çocuklara sunulmustur. Çocukların metinlerle iletilen davranıs, kültür, değer ve bilgileri anladıkları görülmüstür. Metinlerin psikoloji, sosyoloji, kültür değerleri ve dil eğitimi alanlarındaki yerlerinin belirlenmesi ile çalısma tamamlanmıstır. Mesnevîler yazıldıkları dönemde Türkçeyi ve Türk kültürünü yeni yetisen kusaklara aktarmada araç olarak kullanılmıstır. Metinlerde cemiyet hayatının bütün ihtiyaçlarının karsılandığı, sosyal ve manevî dünyanın hiçbir unsurunun atlanmadığı görülmektedir. Bu sebeple Türkçenin 14. yüzyıla ait kaynak metinlerinin çocuk edebiyatı ve dil eğitiminde kullanılabilir olduğu tespit edilmistir.

This research has been carried out to be able to insert them into the course books of second stage of primary education and to let the students know about the texts belonging to our won culture. The study is based on fourteen stories gathered to been published. The stories were obtained not only from mesnevi-an important genre in our literature but also from the investigations performed to transfer this genre to the present time. To find out the stories, a total of eight mesnevi 49.778 couplet were surveyed. Next, from these mesnevi, a dictionary were prepared for the storied composed of the couplets selected from these two mesnevi belonging to the XIV century. Following that, the stories were translated into the modern Turkish and simplified and written taking into account the 600-year period between them. The stories have been picturized by a picture expert of the period through ilustrations reflecting the XIV century, when they were written. The stories were presented to the students at the second stage. It was found out that they understood the tenet of the stories to a considerable extent. It was also determined that Turkish and Turkish culture could be given to the students successfully. When the texts of the stories are viewed, the importance that the then Turkish society attached to the education can easily be realized. These stories penned through the basic rules of our language and carefully selected words, and a plain language turned out to be the best way to educate the society. Many of the objectives found in the Turkish Programs selectively designed by the National Education and the related researchers today are contained in mesnevi many times more. It can also be observed that all the elements of our moral and social world and all the social needs in our lives are well plotted in the this genre. The stories of mesnevi having a plain and clear language are known to be used to transmit Turkish and Turkish culture to the next generation. An empiire dominating the world was established through the use of these texts 600 years ago. It was realized shortly ago that we are come to such a stage that we might lose our won wealth the moment we gave up all the heritrage we were granted by the empire. It is also believed that these texts will not only be used to sustain our language and culture for the coming generation but also to teach the values belonging to the whole humanity The mesnevi meeting the need for knowledge about the literature and daily life have long been ignored and forgotten as have many other Turkish cultural values. These literary works, only used in the Turkish language and Literature departments as research topics, will play a key role for the development for the Turkish education.
Keywords: Türk Dili; Yazım Kuralları